Islamic Area Studies with Geographical Information Systems - Okabe, Atsuyuki (New Horizons in Islamic Studies, 2004)
In this volume the contributors use Geographical Information Systems (GIS) to reassess both historic and contemporary Asian countries and traditionally Islamic areas. This highly illustrated and comprehensive work highlights how GIS can be applied to the social sciences. With its description of how to process, construct and manage geographical data the book is ideal for the non-specialist looking for a new and refreshing way to approach Islamic area studies.